PENGARUH PERBEDAAN SUMBER AIR DAN JENIS PAKAN TERHADAP PERTUMBUHAN DAN KELANGSUNGAN HIDUP KEPITING BAKAU (Scylla serrata) PADA TAMBAK DESA MOJO - Rambu A. A. Praing; Muhammad Zainur; Rudhi Pribadhi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
This study aims to examine and analyze the growth and survival of mud crab (Scylla serrata) with different water sources and different types of feed. This study used a design Plots Divided (Split Plot Design), with the main plot of water resources (soil and brackish water and brackish water of the channel) and the subplot kind of feed (trash fish, squid, crab wideng) with replications for three (3) times . Feeding twice a day ie morning (at 06.00) and afternoon (17:00 hours) at a dose of 15% of the feed weight. The study was conducted from November to December 2013. Biota initial weight ± 100 g. Parameters measured were the growth of the absolute weight of mud crab (Scylla serrata) and survival rates. The results showed growth in the absolute weight of mud crab (Scylla serrata) week 1 to week 4, there is a tendency to rise and survival rate evenly among all treatments. The growth of the absolute weight of mud crab (Scylla serrata) the best of the week 1 to week 4 are the treatment of brackish ground water sources and feeding trash fish. At week 4, which is the end of the study the highest absolute growth of 57.7600 g ± 5:44 (brackish ground water and trash fish) and the lowest was 35.0000 ± 1.80 g (brackish ground water and crab wideng). As for the survival rate of mud crab (Scylla serrata) at 96.3% on a weekly basis.Keywords : feed type, survival, growth,, Scylla serrata, water resources.